Eksplorasi Bakteri Endofit Dari Jahe Merah (Zingiber officinalevar. Rubrum) Asal Pulau Timor - Gergonius Fallo; Yuni Sine; Lukas Pardosi (Fakultas Pertanian, Universitas Timor, 2019)
Ginger (Zingiber officinale) is one of the plants of the zingiberaceae family that grows evenly on the island of Timor. The condition of the island of Timor with a long dry season (± 8 months) resulted in the condition of the plants being in a state of drought stress. The purpose of this study was to obtain endophytic bacteria from ginger plants and to identify macroscopically, and test the endophytic bacterial antagonists as producing antibiotics. Samples were obtained from North Central Timor District (TTU), especially from Naibenu District, Kefamenanu City District, and West Miomaffo District. Bacterial isolation method used is the method of spreading and planting on petri dishes using Nutrient Agar (NA) media. While the test of antibiotic-producing activity is seen from the formation of inhibitory zones around the colony. The results of isolation of endophytic bacteria in ginger plants obtained 14 isolates that have the potential to produce antibiotics. Antagonist test results showed that endophytic bacterial isolates were able to inhibit the growth of Staphylococus aureus bacteria with the highest inhibitory zone diameter, namely from JMKBD3 isolates of 2.66 mm. Morphological identification of JMKBD3 isolate colonies is known that irregular colony shape, undulate edge, flat elevation, and white colony color.